In silico prediction and biological assessment of novel angiogenesis modulators from traditional Chinese medicine - Zhu, Yingli; Yang, Hongbin; Han, Liwen; Mervin, Lewis H.; Hosseini-Gerami, Layla; Li, Peihai; Wright, Peter; Trapotsi, Maria-Anna; Liu, Kechun; Fan, Tai-Ping; Bender, Andreas (Frontiers in Pharmacology, 2023)
Uncontrolled angiogenesis is a common denominator underlying many deadly and debilitating diseases such as myocardial infarction, chronic wounds, cancer, and age-related macular degeneration. As the current range of FDA-approved angiogenesis-based medicines are far from meeting clinical demands, the vast reserve of natural products from traditional Chinese medicine (TCM) offers an alternative source for developing pro-angiogenic or inhibit-angiogenic compounds. Here, we investigated 100 TCM-derived compounds, with 51 of them having reported angiogenesis-modulating activities in the literature, analysing their predicted targets and differentially expressed genes to understand their mechanisms of action. The angiogenesis phenotype was used to generate decision trees for rationalising the poly-pharmacology of known angiogenesis modulators such as ferulic acid and curculigoside and validated by an in vitro endothelial tube formation assay and a zebrafish model of angiogenesis. This new approach was applied to examine the angiogenesis-modulating activities of the remaining 49 compounds. In vitro, tetrahydropalmatine and 1 beta-hydroxyalantolactone stimulated, while cinobufotalin and isoalantolactone inhibited endothelial tube formation. In vivo, ginsenosides Rb3 and Rc, 1 beta-hydroxyalantolactone and surprisingly cinobufotalin, restored angiogenesis against PTK787‐induced impairment in zebrafish. In the absence of PTK787, deoxycholic acid and ursodeoxycholic acid did not affect angiogenesis. Despite some limitations, these results suggest further refinements of in silico prediction combined with biological validation will be a valuable platform for accelerating the research and development of natural products from TCM and understanding their mechanisms of action, and also for other traditional medicines for the prevention and treatment of angiogenic diseases.